Dual Inhibition of γ-Tubulin and Plk1 Induces Mitotic Cell Death - Ebisu, Haruna; Shintani, Kana; Chinen, Takumi; Nagumo, Yoko; Shioda, Shuya; Hatanaka, Taisei; Sakakura, Akira; Hayakawa, Ichiro; Kigoshi, Hideo; Usui, Takeo (Frontiers in Pharmacology, 2021)
α/β-Tubulin inhibitors that alter microtubule (MT) dynamics are commonly used in cancer therapy, however, these inhibitors also cause severe side effects such as peripheral neuropathy. γ-Tubulin is a possible target as antitumor drugs with low side effects, but the antitumor effect of γ-tubulin inhibitors has not been reported yet. In this study, we verified the antitumor activity of gatastatin, a γ-tubulin specific inhibitor. The cytotoxicity of gatastatin was relatively weak compared with that of the conventional MT inhibitors, paclitaxel and vinblastine. To improve the cytotoxicity, we screened the chemicals that improve the effects of gatastatin and found that BI 2536, a Plk1 inhibitor, greatly increases the cytotoxicity of gatastatin. Co-treatment with gatastatin and BI 2536 arrested cell cycle progression at mitosis with abnormal spindles. Moreover, mitotic cell death induced by the combined treatment was suppressed by the Mps1 inhibitor, reversine. These findings suggest that co-treatment with Plk1 and γ-tubulin inhibitors causes spindle assembly checkpoint-dependent mitotic cell death by impairing centrosome functions. These results raise the possibility of Plk1 and γ-tubulin inhibitor co-treatment as a novel cancer chemotherapy.